Une comedia espagnole du Siècle d’Or : El conde de Sex de Antonio Coello y Ochoa (éd. princeps : 1638) - Marc Zuili (Etudes Epistémè)
El conde de Sex, a Spanish comedia written in 1633 by Antonio Coello (1611-1652), is the first play devoted to the complex relationship between Elizabeth I and the earl of Essex. This study, after an introduction to the life and works of Coello, outlines the history of the text of the play, from the manuscript versions to the most recent published editions, and then reflects on the passage from history to fiction as it was accomplished by Coello in the context of seventeenth-century Spanish baroque drama. Finally, this study documents the sources of the play, and the influence of El conde de Sex on other literary works.